Effects of linaclotide in the treatment of chronic constipation and irritable bowel syndrome with constipation: a meta-analysis - Zhao, Qi; Fang, Yongkun; Yan, Cheng; Gao, Jing; Liu, Zhuangzhuang; Zhu, Hanjian; Tang, Dong; Wang, Daorong (Zeitschrift für Gastroenterologie, 2021)
Objective Linaclotide is a guanylate cyclase-C (GCC) agonist that is found in intestinal epithelial cells and is used when treating chronic constipation (CC) and irritable bowel syndrome with constipation (IBS-C). Several randomized controlled trials (RCTs) were conducted for evaluating its efficacy and safety.Methods The PubMed, EMBASE, and Cochrane databases and the Web of Science were searched to find multiple RCTs of patients with CC or IBS-C. The Jadad scoring system was used for evaluating each study’s methodological quality, and RevMan5.3 was used for meta-analysis. The composite endpoint reaction approved by the FDA, abdominal pain and discomfort relief, symptom improvement, and diarrhea-related adverse reactions were chosen as observation indicators, and relative risk (RR) and 95% confidence interval (CI) were obtained for quantitative and comprehensive evaluation.Results Eleven randomized controlled studies were included, consisting of 5 cases of CC and 6 cases of IBS-C. Linaclotide reached the composite endpoint response approved by FDA in the treatment of CC (RR = 3.26, 95% CI: 2.45–4.33), and the composite endpoint response approved by FDA for the treatment of IBS-C (RR = 2.26, 95% CI: 1.86–2.74) was greater than the placebo (both p < 0.00001). The main adverse reactions of linaclotide were gastrointestinal, mostly diarrhea, which was higher than that of the placebo when treating CC (RR = 3.56, 95% CI: 2.76–4.60) and IBS-C (RR = 8.23, 95% CI: 5.69–11.90) (both p < 0.00001).Conclusion Linaclotide proved to be effective and safe for the treatment of CC and IBS-C compared to the placebo. However, diarrhea is the primary adverse reaction.
Keywords: Linaclotid; chronische Obstipation; Reizdarmsyndrom mit Obstipation; randomisierte kontrollierte Studie; Meta-Analyse